NUTRITIONAL ADDITION TO INCREASING THE WEIGHT OF PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY IN THE COASTAL AREA OF KENDARI CITY: CHRONIC ENERGY DEFICIENCY - Fatmawati Fatmawati; Petrus Petrus; Jusuf Kristianto; Ellyani Abadi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Chronic energy deficiency in pregnant women is a problem of nutritional deficiency characterized by upper arm circumference < 23.5 cm, and has an impact on pregnancy complications, risk of giving birth to babies with low birth weight, so nutritional assistance is needed. The aim of this research is to determine the effect of nutritional assistance on the weight of pregnant women. Chronic energy deficiency Methods: This type of research is a quasi-experiment, two group pretest-posttest design with control. The sample was pregnant women in the coastal area of Kendari City, 35 cases and 35 controls using purposive sampling. Data were analyzed using the Mann Whitney test Results: The average body weight of the intervention group before nutritional assistance was 50.95 kg and after assistance was 57.86 cm. Meanwhile, the average weight of the control group was 62.67 kg and after assistance it was 71.09 kg. The results of the Mann Whitney test obtained a p value of 0.000, so there is an influence of nutritional assistance on the weight of pregnant women. Conclusion: Nutritional assistance can increase the weight of pregnant women. Chronic energy deficiency in the coastal area of Kendari city.